2018
DOI: 10.1038/s41419-018-0970-6
|View full text |Cite|
|
Sign up to set email alerts
|

Chaperonin 60 sustains osteoblast autophagy and counteracts glucocorticoid aggravation of osteoporosis by chaperoning RPTOR

Abstract: Glucocorticoid excess medication interrupts osteoblast homeostasis and exacerbates bone mass and microstructure loss ramping up the pathogenesis of osteoporotic disorders. Heat shock protein 60 (HSP60) is found to maintain protein function within cellular microenvironment upon encountering detrimental stress. In this study, we revealed that supraphysiological dexamethasone decreased HSP60 expression along with deregulated autophagy in osteoblasts cultures. This chaperonin is required to sustain autophagic mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 42 publications
1
22
0
Order By: Relevance
“…Autophagy is a highly conserved homeostatic process that plays an essential part in the regulation of osteoblast differentiation and mineralization function (Liu et al, 2013;Nollet et al, 2014;Han et al, 2018;Lian et al, 2018). It has consistently been shown as a protective mechanism in maintaining osteoblast viability by allowing cells to survive various stresses (Todde et al, 2009;White and Lowe, 2009;Gu et al, 2016;Yang et al, 2016;Zhu et al, 2019;Zhao et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Autophagy is a highly conserved homeostatic process that plays an essential part in the regulation of osteoblast differentiation and mineralization function (Liu et al, 2013;Nollet et al, 2014;Han et al, 2018;Lian et al, 2018). It has consistently been shown as a protective mechanism in maintaining osteoblast viability by allowing cells to survive various stresses (Todde et al, 2009;White and Lowe, 2009;Gu et al, 2016;Yang et al, 2016;Zhu et al, 2019;Zhao et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It has consistently been shown as a protective mechanism in maintaining osteoblast viability by allowing cells to survive various stresses (Todde et al, 2009;White and Lowe, 2009;Gu et al, 2016;Yang et al, 2016;Zhu et al, 2019;Zhao et al, 2020). Furthermore, GC usage have been reported to inhibit osteoblast autophagy and this effect plays a pivotal role in the pathogenesis of GIOP (Han et al, 2018;Lian et al, 2018;Gremminger et al, 2019;Wang et al, 2019). Recently a specialized form of autophagy that specifically degrades dysfunctional or redundant mitochondria, termed mitophagy, was found to contribute to the mineralization function of osteoblasts (Pei et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%
“…The four proteins that were significantly different between the treated (PU and FPR inhibitors) and untreated control were HSP 27, HSP 60, catalase and TNF RI/ TNFRSF1A. Our results showed that both HSP 27 and HSP 60 were significantly decreased in the treated group compared to the untreated control, and it is worth taking note that the modulation of HSP 27 [22] and HSP 60 [23] are crucial for the induction of autophagy. On the other hand, catalase, which is often degraded in activation of autophagy, seemed to be upregulated in the PU and FPR inhibitors-treated groups.…”
Section: Autophagy-apoptosis Switch and Anx-a1mentioning
confidence: 53%
“…Cells in each well were harvested and lysed to extract total RNA using TRI reagent ® (Sigma-Aldrich), as previously described [ 24 ]. An amount of 1 μg of total RNA was reversely transcribed using ReadScript ® Two-Step cDNA Synthesis Kits (Sigma-Aldrich, St. Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The ABI 7900 Detection System (Applied Biosystems, Waltham, MA, USA) and 2× TaqMan ® Universal PCR Master Mix, together with customized primers for PCR analysis of BRD4 (forward 5′-ACACCTGCA CCTACCAGACTC-3′; reverse, 5′-CATCGGCTACAGTCTAGGCC-3′), Runx2 (forward, 5′-CCAG CAGCACTCCATAT CTC-3′; reverse, 5′-CAGCGTCAACACCATCATTC-3′), OCN (forward, 5′-TAC AACTCACCAATC AT AAC-3′; reverse, 5′-ACCTTCATACTTCAACTACT-3′), PPARγ2 (forward: 5′-ACCATGGTTGACACAGAGATGCCA-3′; reverse: 5′-AGGAATGCGAGTGGTCTTCCATCA-3′), Foxp1 (forward, 5′-ATAGCTAACCTCGCTCGCCTA-3′; reverse, 5′-CTCTTCATACTACGATGC ATA-3′), and β-actin (forward, 5′-GACGGCCAGGTCATCACTAT-3′; reverse: 5′-CTTCTGCATCCT GTCAGCAA-3′) were used for computing threshold values (C t ) of PCR amplification, according to the manufacturer’s manuals. Fold changes of mRNA expression were calculated using 2 −ΔΔC t (ΔC t , C t of gene—C t of housekeeping gene; ΔΔC t , C t of glucocorticoid group—C t of vehicle group), as previously described [ 24 ].…”
Section: Methodsmentioning
confidence: 99%